Synergistic effect of RHA and FCW in alkali-aggregate reaction mitigation - Guillante, Patrícia (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2019)
Pozzolans rich in silica, such as Rice Husk Ash (RHA), contribute to compressive strength gain but at the same time might increase alkali-aggregate reaction (AAR) in mortar mixtures. Pozzolans that have aluminates, such as Fired Clay Brick Waste (FCW), can be efficient to mitigate AAR but tend to lead to a slower compressive strength development. The association of different types of pozzolans, however, may result in a synergistic effect, compensating individual deficiencies. This paper presents a study of mixtures containing RHA, FCW and these two materials combined, aiming to obtain benefits in the mechanical behavior and in the durability regarding AAR. A substitution rate of 20% Portland cement by pozzolanic material was used. Through accelerated AAR tests and compressive strength measurements, it was found that while RHA is considered harmful to AAR – even when using an innocuous aggregate – FCW presents benefits, also avoiding this deleterious effect when combined with RHA. The same occurs in the compressive strength development, where RHA compensates a small loss of compressive strength associated with the use of FWC alone.